Manilkara zapota “chicozapote” as a fruit source of health-beneficial bioactive compounds and its effects on chronic degenerative and infectious diseases, a review - Rivas-Gastelum, Maria Fernanda; Garcia-Amezquita, Luis Eduardo; Garcia-Varela, Rebeca; Sánchez-López, Angélica Lizeth (Frontiers in Nutrition, 2023)
Manilkara zapota “chicozapote” is an autochthonous evergreen tree from the southern regions of Mexico, Belize, and Guatemala. Currently, it is widely distributed and extensively grown in Mexico and Southeast Asia. Traditionally, different structures of the plant have been used for medical purposes; seeds have diuretic and purgative properties, aiding in digestive complications and eliminating bladder and kidney stones. Tree bark has antidiarrheal, antipyretic, antibiotic, and astringent properties. Fruits and leaves have been used to treat cold, cough, diarrhea, indigestion, fever, hemorrhages, wounds, and ulcers. Chicozapote fruit is yellow and brown, with an oval shape and rough peel, it is an excellent source of nutrients, such as sugars, proteins, amino acids, and minerals, and is rich in phytochemical components, such as flavonoids, phenolic acids, and tannins. These bioactive compounds exert several biological activities, i.e., as an antioxidant, antidiabetic, antimicrobial, anti-inflammatory, cytotoxic, and anti-arthritic agents, to name a few. These beneficial properties assist in preventing chronic and degenerative diseases, such as cancer, diabetes, neurological, infectious, and cardiovascular diseases. The use of chicozapote is still limited to its fresh form, and its non-edible structures produce a lot of waste. Therefore, an alternative valorizing and preserving strategy is to use the fruit as a raw source to design functional foods and pharmacological products. Here, the nutritional and phytochemical profiles and the current view regarding methodologies and conditions, for the extraction and characterization of its bioactive compounds, are described, and focus is placed on their multiple biological effects and specific functional mechanisms.